Analisis Fundamental Makro, Fundamental Mikro Terhadap Kinerja Keuangan Dengan Struktur Kepemilikan, Manajemen Laba, Dan Karakteristik Perusahaan Sebagai Variabel Intervening Pada Perusahaan Tercatat Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Dela Wahyu Putri Awanda; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of macro fundamentals and micro fundamentals on company financial performance, by considering ownership structure, earnings management, and company characteristics as intervening variables. This study focuses on companies listed on the IDX during a certain period. This research uses a quantitative methodology with a path analysis approach to test the correlation between variables. The data analyzed is secondary data taken from the annual reports of companies listed on the IDX. The research results show that macro and micro fundamental factors have a significant influence on the company's financial performance. Ownership structure and company characteristics are proven to act as intervening variables that strengthen the relationship between fundamental factors and financial performance. On the other hand, earnings management was found to have a negative moderating effect on this relationship. These findings provide valuable insight for investors and company management in making investment decisions and company management strategies. This research also provides theoretical contributions in understanding the dynamics of interactions between fundamental factors, ownership structure, earnings management, and company characteristics on financial performance.